Towards the democratization of school management: analysis on the process of re-elaborating the pedagogical political project in a early childhood education unit (Revista Contexto & Educação, 2023)
In order to present the results of a Case Study about the process of re-elaborating the Political Pedagogical Project (PPP) of a municipal school of Early Childhood Education in the interior of São Paulo, carried out during 2017, this article analyzes the actions organized and developed by management team, in order to highlight how these enabled the identification and redefinition of discriminatory educational practices that had already been naturalized by the school community. The methodological path involved the analysis of four central actions of this process: 1) Annual Planning Meeting with parents/guardians, teachers and employees, held at the beginning of the school year; 2) Analysis of data on the profile of the community collected by the management team from the application of a questionnaire with objective questions; 3) Analysis of the Action Plan formulated from the information collected in the questionnaire; 4) Monitoring the collective discussion about the mission, vision and values ​​of the school held during the Annual Replanning. The results showed that the methodology developed by the management team caused significant changes in the school's pedagogical proposal, encouraging community participation in decision-making processes, favoring both the democratization of its management and the offering of an emancipatory education with social quality.